Morphological features, productivity and pollution state of abandoned agricultural soils in the Russian Arctic (Yamal Region) - Nizamutdinov, Timur; Abakumov, Evgeny; Morgun, Evgeniya (One Ecosystem, 2021)
Recently, questions about the return of the concept of Arctic agriculture in order to promote sustainable development of the northern regions and ensure food security have been raised more often. The re-involvement of previously-used and abandoned soils into agricultural usage can provide an essential contribution for the development of the Arctic regions. We conducted a comprehensive research of soils with different levels of abandonment in the central part of the Yamal Region (Russia) and compared their morphological features, chemical and physical properties, fertile qualities and the level of contamination with heavy and trace metals to background soils of the region. It has been noted that there are no evident features of cryoturbation processes in the profiles of abandoned agricultucal soils and regular changes in the redox regime, as a consequence of the presence of reductimorphic spots in the soil profiles, have been recorded. Soil organic matter (SOM) stock in the topsoil of abandoned soils is estimated as medium and has a similar level to the stocks of total organic matter in the agricultural soils of the Arctic circumpolar region (Norway, Sweden, and Finland). Statistically significant differences in the content of nutrients between abandoned and background soils were recorded which indicates stability of the soil nutritional state during different abandoned states. Particularly notable are the differences between the content of available forms of phosphorus. The results of the study revealed significant differences between soils of various periods of abandonment and the background soils of the Yamal Region. Abandoned soils can be used for ground and greenhouse agriculture, these soils having a high level of fertility and are not limited for use in agriculture by the level of contamination with heavy and trace metals. According to the character of trace metal contamination, abandoned and background soils are evaluated as uncontaminated on the base of Z c and I geo indices values. Reuse of the ...